Awareness of health risks related to body art practices among youth in Naples, Italy: a descriptive convenience sample study - Mastronuzzi Roberto; Alfano Vincenza; Visciano Aniello; Onofrio Valeria Di; Mancusi Caterina; Gallè Francesca; Guida Marco; Liguori Giorgio (BMC, 2011)
Abstract Background Body art practices have emerged as common activities among youth, yet few studies have investigated awareness in different age groups of possible health complications associated with piercing and tattooing. Methods We investigated perceptions of and knowledge about health risks. To highlight differences among age groups, we gathered data from students at high schools and universities in the province of Naples. Results Of 9,322 adolescents, 31.3% were pierced and 11.3% were tattooed. Of 3,610 undergraduates, 33% were pierced and 24.5% were tattooed (p < 0.05). A higher number of females were pierced in both samples, but there were no gender differences among tattooed students. Among high school students, 79.4% knew about infectious risks and 46% about non-infectious risks; the respective numbers among university students were 87.2% and 59.1%. Only 3.5% of students in high school and 15% of university undergraduates acknowledged the risk of viral disease transmission; 2% and 3% knew about allergic risks. Among adolescents and young adults, 6.9% and 15.3%, respectively, provided signed informed consent; the former were less knowledgeable about health risks (24.7% vs. 57.1%) (p < 0.05). Seventy-three percent of the high school students and 33.5% of the university students had body art done at unauthorized facilities. Approximately 7% of both samples reported complications from their purchased body art. Conclusions Results indicate a need for adequate information on health risks associated with body art among students in Naples, mainly among high school students. Therefore, adolescents should be targeted for public health education programs.